2023
DOI: 10.1002/cptc.202300010
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Based Circularly Polarized Phosphorescence of a Chiral Schiff Base Platinum(II) Complex Bearing Polyethylene Glycol Chains

Abstract: A chiral Schiff base platinum(II) complex 1 bearing polyethylene glycol (PEG) chains was synthesized. The complex was found to melt at 44 °C whereas its non‐substituted analogue 2 has a high melting point (>300 °C). Upon cooling after melting, the complex remained liquid at room temperature over 30 minutes and exhibited yellow phosphorescence. Circularly polarized phosphorescence (CPP) properties were examined and it was found that the absolute value of the luminescence dissymmetry factor (glum) increases sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…The maximum g lum (2.9 × 10 –3 for 1a ) observed in this study is still a moderate value among the phosphorescent platinum complexes reported in the literature. , Furthermore, the fact that the value of g lum is smaller than g abs in most of the complexes is probably due to the structural asymmetrization in the T 1 excited state. However, we believe that the insights into CPL control based on molecular structural transformation in this study will contribute to the construction of more efficient CPL materials in the future.…”
Section: Resultsmentioning
confidence: 39%
See 1 more Smart Citation
“…The maximum g lum (2.9 × 10 –3 for 1a ) observed in this study is still a moderate value among the phosphorescent platinum complexes reported in the literature. , Furthermore, the fact that the value of g lum is smaller than g abs in most of the complexes is probably due to the structural asymmetrization in the T 1 excited state. However, we believe that the insights into CPL control based on molecular structural transformation in this study will contribute to the construction of more efficient CPL materials in the future.…”
Section: Resultsmentioning
confidence: 39%
“…Organometallic complexes with chiral ligands have attracted increasing attention in recent years as promising CPL materials owing to their large Stokes shifts and highly efficient phosphorescence properties, which are difficult to achieve using SOMs . Various examples of CPL-active organometallic complexes whose metal centers are Cr­(III), Zn(II), Cu­(I), Ru­(III), Re­(I), Pt­(II), Ir­(III), and Au­(I) have been used for developing efficient CPL emitters. However, despite several studies on the correlation between the structure and CPL properties in SOMs, ,,, a clear molecular design for achieving efficient CPL has not been established for organometallic complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Square planar platinum(II) complexes are widely known for their highly efficient phosphorescent emission, and CPP materials have been created by introducing chiral ligands. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] Several chiral platinum(II) complexes have been reported to show CPP with large dissymmetry factors (g lum = 2DI/I = 2(I L À I R )/(I L + I R )) 18 in the aggregated state. 7,8,12,16 In particular, the co-assembly of achiral and chiral platinum complexes reported by You and coworkers showed a considerably large g lum value of 0.064 from a magnetically-allowed metal-metal-to-ligand charge transfer (MMLCT) transition.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17] Several chiral platinum(II) complexes have been reported to show CPP with large dissymmetry factors (g lum = 2DI/I = 2(I L À I R )/(I L + I R )) 18 in the aggregated state. 7,8,12,16 In particular, the co-assembly of achiral and chiral platinum complexes reported by You and coworkers showed a considerably large g lum value of 0.064 from a magnetically-allowed metal-metal-to-ligand charge transfer (MMLCT) transition. 8 However, in the solution-dispersed state, the CPP intensities are low for most of the platinum(II) complexes, usually on the order of 10 À3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation